2020
DOI: 10.3390/metabo10080321
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Exhaled Volatile Organic Compounds in Postoperative Patients Undergoing Analgesic Treatment: A Prospective Observational Study

Abstract: Assessment and treatment of postoperative pain can be challenging as objective examination techniques to detect and quantify pain are lacking. We aimed to investigate changes of exhaled volatile organic compounds (VOCs) in patients with postoperative pain before and after treatment with opioid analgesics. In an observational study in 20 postoperative patients, we monitored for postoperative pain, hemodynamic parameters, and catecholamines before and during treatment. VOCs in the patients were determined by dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Among hundreds of measured VOCs, here we considered compounds with expiratory abundances significantly above the inspiratory/room-air abundance. Out of those markers we selected 23 substances that are important breath biomarkers in clinical breathomics and reflect different origins, physico-chemical characters and dependencies on physiology, metabolism, pathology, therapy and lifestyle/habits( Löser et al., 2020 ; Sukul et al., 2017a , 2018 ; Trefz et al., 2013 , 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among hundreds of measured VOCs, here we considered compounds with expiratory abundances significantly above the inspiratory/room-air abundance. Out of those markers we selected 23 substances that are important breath biomarkers in clinical breathomics and reflect different origins, physico-chemical characters and dependencies on physiology, metabolism, pathology, therapy and lifestyle/habits( Löser et al., 2020 ; Sukul et al., 2017a , 2018 ; Trefz et al., 2013 , 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…High-resolution and real time mass spectrometry based noninvasive, rapid, and repeated evaluation of exhaled volatile metabolites offers immediate overview of various physio-metabolic ( Spacek et al., 2018 ; Sukul et al., 2014 , 2015 , 2017a ), biochemical ( Refat et al., 1991 ; Sukul et al., 2021 ; Weber et al., n.d. ) and pathological/therapeutic processes ( Löser et al., 2020 ; Paardekooper et al., 2017 ; Trefz et al., 2019 ) via breathomics. Previously we have demonstrated the effects of natural menstrual cycle and oral contraception on the exhaled volatile organic compounds (VOCs) profile from healthy adults ( Sukul et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these results demonstrate the value of the ptairMS software as a key resource in breathomics for real-time analysis at the point of care and in biomarker discovery studies, with a high clinical potential for the phenotyping of health and disease, therapeutic drug monitoring, toxicological studies and precision medicine ( Fernández del Río et al , 2015 ; Ibrahim et al , 2019 ; Jung et al , 2021 ; Löser et al , 2020 ; Zhou et al , 2017 ).…”
Section: Discussionmentioning
confidence: 69%
“…Perhaps, only a discrimination between the absence or presence of pain is possible, without a further finetuning of the amount of pain. Finally, it might also be possible that exhaled breath is not altered by neuromodulation (i.e., absence of changes in VOCs) or that the device is not sensitive enough to detect small changes in VOCs, since a study with mass spectrometry revealed clear differences is several specific VOCs in patients with postoperative pain, before and after treatment with opioid analgesics [39], pointing at the potential to differentiate between pain states with mass spectrometry. This is the first study exploring the use of an electronic nose in the context of neuromodulation.…”
Section: Discussionmentioning
confidence: 99%